TINJAUAN HUKUM DIPLOMATIK TENTANG PENYELESAIAN SENGKETA PRAKTIK SPIONASE YANG DILAKUKAN MELALUI MISI DIPLOMATIK DILUAR PENGGUNAAN PERSONA NON-GRATA - Purnama Putera, I Gst Ngr Hady; Putu Sutama, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
The practice of spying or espionage, has long been a problem in the dysfunction of Diplomatic and Consular Relations and also Diplomatic immunity inherent within the Diplomatic and Consular itself. Indeed, International Law has provided a Persona non-Grata mechanism for the receiving State, but, in many cases, this principle has an impact on the relations between the two States, in fact it is not uncommon to be a tension. This paper will discuss a lot about a result of the misuse of diplomatic missions that become the practice of espionage, and how the dispute settlement beside using the Persona non-Grata principle.
Keywords: Espionage, Diplomatic Relation, Dispute Settlement.